2010
DOI: 10.1016/j.brainres.2009.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Altered local coherence in the default mode network due to sevoflurane anesthesia

Abstract: Recently we introduced a robust measure, integrated local correlation (ILC), of local connectivity in the brain using fMRI data which reflects the temporal correlation of brain activity in every voxel neighborhood. The current work studies ILC in fMRI data obtained in the absence and presence of sevoflurane anesthesia (0%, 2%, and 1% end-tidal concentration, respectively) administered to healthy volunteers. ILC was determined specifically in regions of the default mode network (DMN) to address local changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 52 publications
11
66
0
Order By: Relevance
“…The CO 2 -induced reduction in sensorimotor connectivity is also in good agreement with a previous report by Biswal et al (1997). In our study, we have taken special precaution to minimize the influence of basal vascular state on BOLD signals, which were not accounted for in previous studies comparing fcMRI data across physiologic states (Biswal et al, 1997;Deshpande et al, 2010;Greicius et al, 2008;Horovitz et al, 2009). We have used visual-evoked fMRI signal as a reference with the assumption that the alterations in fMRI signal is solely due to a change in vascular state (Jones et al, 2005;Zappe et al, 2008a).…”
Section: Discussionsupporting
confidence: 88%
“…The CO 2 -induced reduction in sensorimotor connectivity is also in good agreement with a previous report by Biswal et al (1997). In our study, we have taken special precaution to minimize the influence of basal vascular state on BOLD signals, which were not accounted for in previous studies comparing fcMRI data across physiologic states (Biswal et al, 1997;Deshpande et al, 2010;Greicius et al, 2008;Horovitz et al, 2009). We have used visual-evoked fMRI signal as a reference with the assumption that the alterations in fMRI signal is solely due to a change in vascular state (Jones et al, 2005;Zappe et al, 2008a).…”
Section: Discussionsupporting
confidence: 88%
“…Disconnection of frontal DMN regions has also been observed in sevoflurane-induced sedation (Deshpande et al, 2010;Palanca et al, 2015), non-REM sleep (Horovitz et al, 2009;Samann et al, 2011), and MCS, VS/UWS and coma (Soddu et al, 2012;Vanhaudenhuyse et al, 2010). Interestingly, we found that a mesopontine area was also among the regions decreasing in the total brain connectivity map.…”
Section: Total Brain Connectivitysupporting
confidence: 53%
“…Seed-based and independent component analyses (ICA) were used and identified dissociation between the anterior and posterior regions of the DMN. Further, while this dissociation was seen for both awake and anesthetized dogs, the degree of dissociation was higher in anesthetized dogs in keeping with prior human results that anesthesia modulated the structure of resting state networks such as the DMN (Deshpande, Kerssens, Sebel, & Hu, 2010). In all, this investigation into resting state fMRI with dogs revealed comparative differences in the traits of the DMN between humans/monkeys and dogs, namely localized anterior and posterior subnetworks in dogs and a connected DMN in humans.…”
Section: History Of Fmri In the Dogsupporting
confidence: 85%